Gene expression profile of oxidative stress in the lung of inbred mice after intestinal ischemia/reperfusion injury - Ikejiri,Adauto Tsutomu (2014)
PURPOSE: To determine the gene expression profile associated with oxidative stress and antioxidant defense in the lung tissue of mice subjected to intestinal ischemia and reperfusion.METHODS: Twelve male, inbred mice (C57BL/6) were randomly assigned to one of two groups. The control group (CG) underwent anesthesia and laparotomy and was observed for 120 minutes; the ischemia/reperfusion group (IRG) was subjected to anesthesia, laparotomy, and ischemia of the small intestine for 60 minutes and to 60 minutes of reperfusion. A pool of six mice from each group was subjected to a reverse transcription-quantitative polymerase chain reaction (RT-qPCR) to analyze the oxidative stress and antioxidant defense genes. All genes that were up-regulated or down-regulated greater than three-fold, based on the algorithm [2